Pengujian Kekuatan Struktur Perkerasan Berdasarkan Lendutan dengan Benkelman Beam dan Falling Weight Deflectometer - Furqon Affandi (Jurnal Jalan-Jembatan, 2005)
The evaluation of pavement strength has been conducted and developed for long. There are two different types of evaluation namely destructive and non destructive methods. The tools for non destructive techniques have rapidly developed such as Falling Weight Deflectometer (FWD), however, this equipment is very expensive so that big budget is required for it. Moreover, the number of road links served is long. Another simple equipment is Benkelman Beam (BB) which well known in Indonesia, cheap and more practical in use . This paper presents the relationship between the test results of the strength of the structural number of existing pavement structures in Central Java using FWD and BB obtaining from surface deflections and tangent of deflection bowl. The study reveals that a variety of relationships occurred so that careful consideration is needed in correlating the relationships of the strength of pavement structures based on FWD and BB.